Increased Expression of TLR10 in B Cell Subsets Correlates with Disease Activity in Rheumatoid Arthritis - Ying Zhang; Rong Cao; Haijian Ying; Juping Du; Shuaishuai Chen; Na Wang; Bo Shen (Mediators of Inflammation)
Toll-like receptor (TLR) 10, mainly expressed on B cells, has emerged as a modulatory receptor in inflammation. Nonetheless, the clinical significance of TLR10 in rheumatoid arthritis (RA) remains unclear. In this study, we explored the expression of TLR10 in B cells and B cell subsets in RA subjects and healthy controls (HCs) and determined its relevance to disease activity and inflammatory biomarkers. TLR10 levels in B cells and B cell subsets (CD19+CD27+, CD19+CD27−, CD27+IgD−, CD27+IgD+, CD27−IgD+, D27−IgD−, CD19+CD5+, and CD19+CD5−) and inflammatory biomarker concentrations in peripheral blood (PB) obtained from RA subjects and HCs were detected by flow cytometry and enzyme-linked immunosorbent assay (ELISA), respectively. The correlations of TLR10 expression with disease activity and inflammatory biomarkers were then analysed. Similar levels of TLR10 in all CD19+ B cells were observed in the RA subjects and HCs. Compared to that in the HCs, TLR10 was elevated significantly in the CD19+CD27−IgD− and CD19+CD5+ subsets in the RA subjects. In addition, almost all subsets expressing TLR10 were increased with disease activity. The present study reveals that enhanced TLR10 in B cell subsets is positively correlated with disease activity in RA subjects.